العمليّة التكوينيّة في المنظومة التربوية الجزائرية وإتجاهات أساتذة التعليم الثانوي نحوها - عليك, نامية; شيباني, ليلى (جامعة الوادي - University of Eloued, 2023)
تهتم الدول بمنظوماتها التربوية من خلال تكوين الأساتذة وتدريبهم بغية تحسين مستواهم وترقيتهم لبناء أجيال ذات كفاءات عالية تفتخر بهم أوطانهم باعتبارهم مسؤولين على نجاح أي نظام تعليمي. والجزائر واحدة من هذه الدّول التي تسعى إلى تكوين الأساتذة والمعلمين خاصة مع حركة الإصلاح التي شرعت فيها وزارة التربية بدء من سنة 2003، على أساس أن تكوين الأساتذة يعد عاملا حاسما في رفع مردودية المنظومة التربوية في سياقها النسقي. إيمانا منا بأهمية عملية التكوين في جوهرها وأهدافها، فإننا نسعى من خلال هذه الدراسة إلى معرفة اتجاهات أساتذة التعليم الثانوي لولاية البليدة الذين يخضعون للتكوين أثناء فترة التربص نحو العملية التكوينية، على عينة قدرت بـ150 أستاذا يتكونون في متوسطة "مفدي زكريا" ببوفاريكـ وذلك بالاعتماد على استبيان تم بناؤه من طرف الباحثتين وفق مجموعة من المحاور تهدف في عمومها إلى قياس ظروف التكوين ومدى كفاية مختلف المواد التكوينية في الرفع من مستوى المكونين وسيرورة التكوين معتمدين المنهج الوصفي. وخلصت نتائج الدراسة إلى أن: اتجاهات أساتذة اساتذة التعليم الإبتدائي الذين يخضعون للتكوين أثناء التربُّص وقبل الترسيم نحو عملية التكوين، هو اتجاه سلبي. لا توجد فروق ذات دلالة إحصائية في اتجاهات أساتذة التعليم الثانوي نحو التكوين أثناء التربص وقبل الترسيم تعزى لظروف التكوين. لا توجد فروق ذات دلالة إحصائية في اتجاهات أساتذة التعليم الثانوي نحو التكوين أثناء التربص وقبل الترسيم تعزى لمواد التدريس. Abstract : States are concerned with their educational systems through the formation and training of teachers in order to improve their level and advancement to build generations of high competencies that are proud of their home countries as responsible for the success of any educational system. Algeria is one of those countries that seek to form teachers and teachers especially with the reform movement initiated by the Ministry of Education starting from 2003, on the basis that the formation of professors is a decisive factor in raising the cost of the educational system in its context. We believe in the importance of the training process in its essence and objectives. In this study, we seek to know the trends of the teachers of secondary education in Blida governorate, who are subject to training during the traineeship period towards the formative process, on a sample estimated at 150 teachers, It was built by the two researchers in accordance with a set of axes aimed at measuring the conditions of the composition and the adequacy of the various training materials in raising the level of components and the process of formation. The results of the study concluded that: Trends of secondary education teachers who are subject to training during training and before demarcation towards the training process is a negative trend. • There are no statistically significant differences in the attitudes of secondary education teachers towards training during training and before demarcation due to the conditions of the composition. • There are no statistically significant differences in the attitudes of secondary education teachers toward training during training and before demarcation due to teaching materials.
دراسة ميدانية في مؤسسات التعليم الثانوي لولاية البليدة
مقال
Keywords: المنظومة التربوية؛ اإلصالح؛ التكوين؛الأستاد ؛ االتجاه; educational system; reform; composition; professor; direction